Cardiovascular toxicities associated with immune checkpoint inhibitors. Issue 5 (2nd February 2019) - Hu, Jiun-Ruey; Florido, Roberta; Lipson, Evan J; Naidoo, Jarushka; Ardehali, Reza; Tocchetti, Carlo G; Lyon, Alexander R; Padera, Robert F; Johnson, Douglas B; Moslehi, Javid
Abstract: Cardiovascular toxicities associated with immune checkpoint inhibitors (ICIs) have been reported in case series but have been underappreciated due to their recent emergence, difficulties in diagnosis and non-specific clinical manifestations. ICIs are antibodies that block negative regulators of the T cell immune response, including cytotoxic T lymphocyte-associated protein-4 (CTLA-4), programmed cell death protein-1 (PD-1), and PD-1 ligand (PD-L1). While ICIs have introduced a significant mortality benefit in several cancer types, the augmented immune response has led to a range of immune-related toxicities, including cardiovascular toxicity. ICI-associated myocarditis often presents with arrhythmias, may co-exist with myositis and myasthenia gravis, can be severe, and portends a poor prognosis. In addition, pericardial disease, vasculitis, including temporal arteritis, and non-inflammatory heart failure, have been recently described as immune-related toxicities from ICI. This narrative review describes the epidemiology, diagnosis, pathophysiology, and treatment of cardiovascular toxicities of ICI therapy, highlighting recent developments in the field in the past year.